Komposisi dan Struktur Komunitas Fitoplankton di Danau Maninjau Sumatera Barat - Gusna Merina; Afrizal S; - Izmiarti (Universitas Andalas, 2014)
A study on composition and structure of phytoplankton community at Maninjau lake was conducted from April to July 2013. The planktons were sampled purposively at 11 stastions using vertically towed of plankton net. This study found a total 94 species of phytoplankton that mostly belong to Chlorophyceae. Density of phytoplankton varied significantly between sampling stations ranged from 1,083 to 5,119 ind/l. The highest density was found at Station where agriculture plant dominated the vegetations around the edge of the lake, while the lowest density found at station located near the centre of the lake. Those phytoplanktons with relative density higher than 5% were Synedra ulna, Cosmarium compressus, Cosmarium decoratum, Sturastrum playfairi, Chroococcus disperses, Chroococcus limneticus and Glenodinium quadridens. Diversity indiches of phytoplankton (H`) was ranged from 1,96-2,80 with highest diversity at Galapuang (near garbages disposal area and fish farms) and the lowest was at Pakan Rabaa (water inlet). Equitability indiches (E) ranged from 0.65 to 0.81. The Index of Similarity phytoplankton was range from 28.12-70.00%. The result of this study might suggest that composition of the phytoplankton in the lake was relatively high although the structure reflected some influencees of human activities.Key word :phytoplankton, community, diversity, and Maninjau Lake.